2020
DOI: 10.1108/ijilt-02-2020-0013
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of blended learning deployment in institutions of higher learning: theory of planned behavior perspective

Abstract: PurposeBlended learning (BL) has been increasing in popularity and demand and has developed as a common practice in institutions of higher learning. Therefore, this study develops a model to evaluate the critical predictors that determine students' acceptance and deployment of BL in institutions of higher education based on the theory of planned behavior (TPB).Design/methodology/approachThe empirical analysis entails data collected from 1,811 responses from an online survey questionnaire from students in Malay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…In terms of self-efficacy, the students believe that they can participate in blended learning and find no significant difficulties to adapt to the new learning style. It is consistent with Anthony et al (2020), who also found that self-efficacy is one of the main factors influencing students' perception of blended learning in Malaysian HEIs. The findings from the study showed that the students contented that they save money and times when the assignments are required to be sent into the online platform.…”
Section: Discussionsupporting
confidence: 88%
“…In terms of self-efficacy, the students believe that they can participate in blended learning and find no significant difficulties to adapt to the new learning style. It is consistent with Anthony et al (2020), who also found that self-efficacy is one of the main factors influencing students' perception of blended learning in Malaysian HEIs. The findings from the study showed that the students contented that they save money and times when the assignments are required to be sent into the online platform.…”
Section: Discussionsupporting
confidence: 88%
“…However, these studies were usually based on relatively small, highly specific samples (e.g., 152 teachers of a Californian urban school district in Dunn et al, 2018; 146 general practitioners in Iran in Hadadgar et al, 2016) or school or university student samples (e.g., Anthony Jnr et al, 2020; Chai et al, 2020; Cheon et al, 2012; Liao et al, 2011). Furthermore, these studies considered participants’ intention but not the actual performance of the behavior, and focused on specific courses or forms of learning instead of general formal, non-formal, or informal LLL (e.g., intention to participate in blended learning in Anthony Jnr et al, 2020; intention to learn Artificial Intelligence in Chai et al, 2020; intention to participate in mobile learning in Cheon et al, 2012; intention to participate in math workshops for teacher professional learning in Dunn et al, 2018; intention to use e-learning to participate in continuing medical education in Hadadgar et al, 2016; intention to continue using an e-learning website in Liao et al, 2011). Beyond that, there are initial results by Van Nieuwenhove and De Wever (2021) who applied TPB to predict more general LLL intentions in the next 12 months based on a sample of 23–65-year-old adults ( N = 335).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, to ease the burden on the health sector, many countries have decided to temporarily close schools as to promote physical distancing initiatives (Mian and Khan, 2020;Van Lancker and Parolin, 2020). This has resulted to a paradigm shift in terms of learning (Jnr et al, 2020;Mulenga and Marb an, 2020), forcing educational institutions to employ alternate approaches for engaging students learning during the pandemic (Mian and Khan, 2020). Due to the disruption of COVID-19 on the society (Jnr, 2020), institutions such as universities and colleges are now employing digital technologies (Anderson et al, 2020;Keefe, 2020;Mulenga and Marb an, 2020;Zayapragassarazan, 2020) such as emergency remote teaching (ERT) and virtual learning (VL) for educational activities.…”
Section: Introductionmentioning
confidence: 99%